Potential Sabotage of Host Cell Physiology by Apicomplexan Parasites for Their Survival Benefits - Chakraborty, Shalini; Roy, Sonti; Mistry, Hiral Uday; Murthy, Shweta; George, Neena; Bhandari, Vasundhra; Sharma, Paresh (Frontiers in Immunology, 2017)
Plasmodium, Toxoplasma, Cryptosporidium, Babesia and Theileria are the major apicomplexan parasites affecting humans or animals worldwide. These pathogens represent an excellent example of host manipulators who can overturn host signalling pathways for their survival. They infect different types of host cells and take charge of the host machinery to gain nutrients and prevent itself from host attack. The mechanisms by which these pathogens modulate the host signalling pathways are well studied for Plasmodium, Toxoplasma, Cryptosporidium, and Theileria, except for limited studies on Babesia. Theileria is a unique pathogen taking into account the way it modulates host cell transformation, resulting in its clonal expansion. These parasites majorly modulate similar host signalling pathways, however, the disease outcome and effect is different among them. In this review, we discuss the approaches of these apicomplexan to manipulate the host parasite clearance pathways during infection, invasion, survival, and egress.